Hijaiyah Learning Media Using Augmentend Reality TK Masyitoh 12 - Mohammad Doni Ferdiansah SM; Nuril Lutvi Azizah (Procedia of Engineering and Life Science, 2022)
Indonesia is one of the largest Islamic countries in the world. Al-Quran learning is an early learning that must be implemented from an early age. The introduction of Hijaiyah letters is one of them for early learning, but some children aged 4 to 7 years prefer and are engrossed in their smartphones other than learning to read the Koran. Thus, it is very difficult for children to distinguish the hijaiyah letters. In the era of technology, of course, everyone is familiar with 3dimensional (3D) technology, now comes a new technology called Augmented Reality, namely technology that can combine the real world with the virtual world which is responded to through electronic devices. With the development of today's technology, as well as finding information is difficult. There have been many ways that have been done by previous researchers to create learning media to foster interest in learning hijaiyah letters. one of them is using Augmented Reality (AR) by mixing hijaiyah letters which are expected to be in 3 dimensions to recognize the differences in letters with android interactive educational applications in this application there are also sounds for children to understand the differences in hijaiyah letters in the letters.